Locating ICT's benefits in elderly care. - Olve, Nils-Goran
The impact of information and communication technology (ICT) is indirect and depends on redesign of practices and structures also outside health care. Improvements will only be realized if all parties involved can coordinate their efforts to take advantage of new technology. A 'package' of changed work practices and structures extending across organizational boundaries needs to be designed and implemented. This is very different from the common conception of introducing new ICT tools. Calls for 'evaluation of benefits' before new ICT systems are introduced need to recognize this complexity. This article investigates how analysis and economic evaluations can be used to improve decision-making when new applications are proposed. This is done by drawing parallels with experiences from other industries. We conclude that the entire 'change package' should be analysed for its consequences on the well-being of care recipients, and the requirements it presents for capital investments and changed labour inputs, in particular changed competence needs. Some concepts and structures are suggested for such evaluations.
Keywords: Information and communication technology; Elderly health care; Process redesign; Economic evaluation; Virtual organization; Integrated care